The Effect of Deep Breathing Relaxation on Changes of Blood Pressure on Hypertention Patients - Samsinar Butar Butar; Yohannes Gamayana; Loritta Yemina (STIKep PPNI Jawa Barat, 2022)
Aims: Hypertension is an increase in blood pressure above normal. The intended upgrade is if enhancement pressure systolic > 140 mmHg and diastolic > 90 mmHg in 2 measurements measured in state calm or rest with hose 5 minutes time. If the blood pressure permanent for a period of time, can cause damage to organs such as kidneys, heart, and brain. Deep breathing relaxation is a non - pharmacologic therapy, It’s capable of lighten up or lowering the blood pressure so that need to be conducted independently at home besides pharmacology therapy like taking hypertension drugs. The purpose of this study was to analyze the effect of deep breathing techniques on changes in blood pressure in hypertensive patients. Method: The Method of this study were pre-experimental design and one group pretest-posttest design with purposive sampling technique. Result: The results of this study shows that there is an effect of deep breathing techniques to lower blood pressure with P value = 0.000 or < 0.05. Conclusion: The conclusion shows that there is an effect of deep breathing techniques to lower blood pressure. Nurses suggest to encourage the hypertention patients to do the deep breathing exercises on their own.